Productivity Analysis Of Fisherman Catchment In Pangandaran District (Case Study Of Pangandaran District) - Yuli Nisa Nuryanti; Asep Agus Handaka Suryana; Rusky Intan Pratama; Ine Maulina (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
This research was conducted at Pangandaran Sub Regency, Pangandaran Regency in August untill December 2021. The aims of this study was to analyze the profile and factors that affect the dynamics of fishing productivity in Pangandaran District, Pangandaran Regency. The research method used in this research is the litelature survey. The data obtained is in the form of primary and secondary data. Data collection is done using questionnaires using purposive sampling techniques. Data analyzed by using quantitative and qualitative descriptive methods. The results showed that in 2015 produced the highest value of production productivity per fisherman of 2,393.6 kg / person / year and the highest value of production productivity per ship unit of 7,440.2 kg / unit / year. The highest result of productivity of production value per fisherman amounted to Rp. 113,411,224 per fisherman per year, and productivity of production value per ship unit amounted to Rp. 352,519,887 per ship unit per year. Factors that affect fishing productivity are the number of crew members per trip, the size of the ship, the length of the fishing operation per trip, many fishing operations per month and operational costs.